Homeland Security The Essentials - Bullock, Jane A.; Haddow, George D.; Coppola, Damon P. (Butterworth-Heinemann, 2018)
Homeland Security: The Essentials, Second Edition concisely outlines the risks facing the US today and the structures we have put in place to deal with them. The authors expertly delineate the bedrock principles of preparing for, mitigating, managing, and recovering from emergencies and disasters. From cyberwarfare, to devastating tornadoes, to car bombs, all hazards currently fall within the purview of the Department of Homeland Security, yet the federal role must be closely aligned with the work of partners in the private sector. The book lays a solid foundation for the study of present and future threats to our communities and to national security, also challenging readers to imagine more effective ways to manage these risks.